Treatment of endo-periodontal lesion using leukocyte- platelet- rich fibrin. A case report (Colombia Medica, 2017)
Case Description: The main objective of this paper was to report the clinical effectiveness of leukocyte- platelet- rich fibrin (L-PRF) in the treatment of a combined endo-periodontal lesion of an upper first premolar.Clinical Findings: The tooth had a profound abfraction on the vestibular aspect and presented no mobility but revealed a deep pocket measuring of 11 mm on the mesial vestibular aspect and 14 mm on the mesial palatine aspect. The three dimensional image analysis showed total bone loss in the mesial aspect and an extensively bone loss of the vestibular aspect of the vestibular root.Treatment and Outcome: Endodontic treatment was performed and periodontal access surgery (surgical periodontal therapy) was done with the application of autologous L-PRF. Three month and 6 months after surgery, the cone beam computed tomography (CBCT) exams showed no bone regeneration in any aspect of the tooth. However, periodontal examination showed a significative improvement in the deepness of surcus. The mesial vestibular aspect had a deep pocket of 3 mm and 5 mm on the mesial palatine aspect showing a reduction in deepness of 8 mm and 9 mm, respectively.Clinical Relevance:  The actual treatment for teeth with bad prognosis is the extraction and replacement with implants. Even though implants are capable of restore function and aesthetic, the abuse of this approach have led to the loss of teeth that could be successfully treated with a less invasive technique. The prognosis of teeth with endoperiodontal lesion is poor but could be enhanced with regenerative therapies. Until now there are no clinical trials and just four case report about the treatment of these teeth with platelet rich fibrin.